Dampak Coronavirus Disease 2019 terhadap Sistem Kardiovaskular - Willim, Herick A.; Ketaren, Infan; Supit, Alice I. (Universitas Sam Ratulangi, 2020)
Abstract: Coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection has become a pandemic. Patient with cardiovascular comorbidity has a higher risk of suffering more severe manifestation of COVID-19 associated with a higher mortality. Although dominated by respiratory clinical manifestation, COVID-19 may also cause severe cardiovascular disorders. Angiotensin converting enzyme 2 (ACE2) acts as a receptor of SARS-CoV-2. Patients of COVID-19 with cardiovascular comorbidities may experience more severe clinical manifestations, presumably due to higher ACE2 expression in this population. Cardiovascular complications in COVID-19 may include myocardial injury, myocarditis, acute myocardial infarction, acute heart failure, thromboembolism, and arrhythmias. Therefore, optimization of conservative medical therapy needs to be prioritized in patients with cardiovascular comorbidities. Emergency intervention can be considered in certain cases with hemodynamic instability.Keywords: cardiovascular system, COVID-19, SARS-CoV-2, ACE2Â Abstrak: Coronavirus disease 2019 (COVID-19) telah merupakan pandemi yang disebabkan oleh infeksi Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Pasien dengan komorbid kardiovaskular berisiko lebih tinggi untuk mengalami manifestasi yang lebih berat jika terinfeksi COVID-19 dan berhubungan dengan mortalitas yang lebih tinggi. Meskipun didominasi oleh manifestasi klinis respiratorik, COVID-19 juga dapat menyebabkan gangguan kardiovaskular yang berat. Angiotensin converting enzyme 2 (ACE2) berperan sebagai reseptor SARS-CoV-2. Diduga pasien dengan penyakit kardiovaskular dapat bermanifestasi klinis lebih berat karena ekspresi ACE2 yang lebih tinggi pada populasi ini. Komplikasi kardiovaskular pada COVID-19 dapat meliputi jejas miokardium, miokarditis, infark miokard akut, gagal jantung akut, tromboemboli, dan aritmia. Pada pasien dengan komorbid kardiovaskular, optimalisasi terapi medis konservatif perlu diprioritaskan. Tindakan intervensi darurat dapat dipertimbangkan pada kasus tertentu dengan instabilitas hemodinamik.Kata kunci: sistem kardiovaskular, COVID-19, SARS-CoV-2, ACE2